On the electron diffusion region in planar, asymmetric, systems. Issue 24 (16th December 2014) - Hesse, Michael; Aunai, Nicolas; Sibeck, David; Birn, Joachim
Abstract Particle‐in‐cell simulations and analytical theory are employed to study the electron diffusion region in asymmetric reconnection, which is taking place in planar configurations without a guide field. The analysis presented here focuses on the nature of the local reconnection electric field and on differences from symmetric configurations. Further emphasis is on the complex structure of the electron distribution in the diffusion region, which is generated by the mixing of particles from different sources. We find that the electric field component that is directly responsible for flux transport is provided not by electron pressure‐based, "quasi‐viscous, " terms but by inertial terms. The quasi‐viscous component is shown to be critical in that it is necessary to sustain the required overall electric field pattern in the immediate neighborhood of the reconnection X line.